2005
DOI: 10.1518/001872005775570934
|View full text |Cite
|
Sign up to set email alerts
|

Individual Perception of Noise Exposure and Hearing Protection in Industry

Abstract: Existing approaches that explain the behavior of workers in noisy environments rarely include quantitative variables related to central factors such as noise exposure levels and workers' hearing status. The aim of this study is to analyze the relationship among individual, contextual, and perceptual-cognitive factors and the use of hearing protection devices (HPDs). We studied 516 industrial workers exposed to noise levels greater than the Portuguese action level and developed a conceptual model for HPD use. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Lo anterior coincide con el estudio de Corrales et al (17), quienes encontraron que los trabajadores 12. García Y. Análisis y evaluación de la incidencia de la reconocían que el ruido podía dañar su audición; pero las conclusiones no coinciden con las de Arezes et al y otros autores (9,(18)(19)(20)(21)(22), quienes en su estudios encontraron que los trabajadores no consideraban como peligrosos los altos niveles de ruido, tampoco con el de Zamorano et al (23), quienes encontraron un bajo nivel de conocimiento en la prevención de los riesgos laborales.…”
Section: Discussionunclassified
“…Lo anterior coincide con el estudio de Corrales et al (17), quienes encontraron que los trabajadores 12. García Y. Análisis y evaluación de la incidencia de la reconocían que el ruido podía dañar su audición; pero las conclusiones no coinciden con las de Arezes et al y otros autores (9,(18)(19)(20)(21)(22), quienes en su estudios encontraron que los trabajadores no consideraban como peligrosos los altos niveles de ruido, tampoco con el de Zamorano et al (23), quienes encontraron un bajo nivel de conocimiento en la prevención de los riesgos laborales.…”
Section: Discussionunclassified
“…Programs targeting younger workers may be effective in increasing their perception of risk (Lombardi et al 2009). On the contrary, another study showed significant negative correlation between age and risk perception indicating higher risk perception among younger workers (Arezes and Miguel 2005a).…”
Section: Workers Perception Of Benefit Of and Barriers To Adoption Ofmentioning
confidence: 95%
“…The essence of applying such requirements in conjunction with the principles of ergonomics has been captured in Figure 1. Adherence to ergonomic requirements helps reduce work strenuousness, achieve comfort and boost workers' ability to operate machinery and equipment efficiently [16]. To ensure the safe operation of technical equipment, it is critical to comply with:…”
Section: Operating Safety Guidelinesmentioning
confidence: 99%